Organizational Culture Perspective on the Quality of Educational Administration Services - Anita Syam; Mashuri Mashuri (Jurnal Pendidikan dan Pembelajaran, 2021)
The quality of educational administration services is one of the problems that is often perceived as a contributor to the weak quality of education. The service process is too convoluted, the turnaround time is long to the poor service of the administrator. And the focus of improving the quality of administrative services is usually only on improving the quality of administrators as the spearhead of the performance of an educational administration service. The administrator as the executor of educational administration services is the result of the interaction of the upper, middle, and lower levels of management so that it cannot be separated from the influence of social interaction, work climate which is collected in the form of organizational culture. This study aims to provide an overview of the relationship between organizational culture and the quality of educational administration services using the Library Research method. The results of the analysis show that organizational culture provides intervention on the quality of educational administration services, so the results of this study provide the concept of improving the quality of administrative services not only from improving the quality of administrator resources but also from other elements in the organization.